Synthesis of piperlogs and analysis of their effects on cells - Boskovic, Zarko V. (2013)
Piperlongumine (PL) is a naturally occurring small molecule previously shown to induce cell death preferentially in cancer cells relative to non-cancer cells. An initial effort to synthesize analogs highlighted the reactivities of both of piperlongumine's α,β-unsaturated imide functionalities as key features determining PL's cellular effects. In this study, a second-generation of analogs was synthesized and evaluated in cells to gain further insight into how the reactivity, number, and orientation of PL's reactive olefins contribute to its ability to alter the physiology of cells.